2021
DOI: 10.1021/acs.inorgchem.0c03266
|View full text |Cite
|
Sign up to set email alerts
|

Selection Criteria for Metal Precursors and Solvents for Targeted Synthesis of Metallic Nanostructures Via Kinetic Control in the Polyol Process

Abstract: Development of a technology for the synthesis of monometallic or multimetallic nanoparticles is exceptionally vital for the preparation of novel magnetic, optical. and catalytic functional materials. In this context, the polyol process is a safe and scalable method for preparation of metal nanoparticles with controlled sizes and shapes in large scales. However, there is no systematic investigation that discusses the criteria for the selection of metal salt and solvent type that determine the kinetics of reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…It has been reported that the reduction time can also be tuned by selecting the appropriate counterion of the metal salt. 25 For example, in the ethylene glycol system, considering the value of pK a , the order of easy reduction of metal salts is M(acac) 2 > M(OAc) 2 > MSO 4 > MCl 2 (M = Metal). In other words, the reduction of Cu acetate could proceed easily, while the Cu sulfate and chloride take a longer time to reduce.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that the reduction time can also be tuned by selecting the appropriate counterion of the metal salt. 25 For example, in the ethylene glycol system, considering the value of pK a , the order of easy reduction of metal salts is M(acac) 2 > M(OAc) 2 > MSO 4 > MCl 2 (M = Metal). In other words, the reduction of Cu acetate could proceed easily, while the Cu sulfate and chloride take a longer time to reduce.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the last few decades, polyols have been utilized to synthesize bimetallic nanostructures. 23,24 Here, the reduction rate can be controlled by selecting the polyol type, metal salt, 25 temperature, and surfactant. However, the reducing power of polyols was still high, and manipulating the characteristics of bimetallic nanostructures such as the shape, composition, and elemental distribution has become difficult.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Kaneko et al analyzed the reducing potential of various diols and showed that their reducing potential strongly depends on the number of carbon atoms between the -OH groups: the smaller distance between the hydroxyl groups results in higher reducing ability. 46 The reactivity of polyols with different positions of the hydroxyl groups are almost similar as far as the number of carbon atoms between them is the same.…”
Section: Key Parameters Inuencing the Size Shape And Structure Of Na...mentioning
confidence: 98%
“…Thus, using the polyol process, these drawbacks can be avoided. From a mechanistic point of view, the polyol process is based on the dehydration and oxidation of the alcohol to aldehydes or ketones (depending on the nature of the polyol used), and this process promotes the reduction of Co ions to Co metal [251,252] . Thus, a proper choice of the polyol is important, having the reducing potential suitable to carry out the reduction of the cobalt precursor.…”
Section: Preparation Of Cobalt Nanoparticlesmentioning
confidence: 99%